OBSERVATION OF THE UTILIZATION OF SUPERIOR FISH RESOURCES AND ITS DEVELOPMENT STRATEGY IN SOUTH BANGKA REGENCY WATERS (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
South Bangka Regency is surrounded by sea waters which are in the central position of three fish migration routes (Strait of Malacca, Java Sea, and Natuna waters). Therefore, it has a great opportunity to develop its fish resources. This study aims to analyze the types of superior fish resources, production trends, and formulate priority strategies for the development of superior fish resources in South Bangka Regency waters. The methods used are the scoring method, curve estimation model, and the AHP method. Squid, shrimp, grouper, red snapper, and mackerel were selected as superior fish resources. The production trend of squid, red snapper, and grouper followed the polynomial model, while shrimp and mackerel were each logarithmic and exponential. The priority strategies for the development of superior fish resources in South Bangka Regency waters were promotion of optimizing the utilization of superior fish resources (RK= 0.250), introduction of technology and creative activities in fishing (RK= 0.217), and development of fisheries business based on regional potential (RK= 0.167).